Efficacy Of Chlorhexidine, Neem, And Green Tea Mouthwashes In The Management Of Gingivitis - Maryam Panhwar; Syed Zafar Abbas; Asha Devi; Sidra Mohiuddin; Ashar Afaq; Qasier Ali Baig (Annals of Abbasi Shaheed Hospital and Karachi Medical & Dental College)
Objective: This study compared the efficacy and anti-inflammatory effects of Chlorhexidine, Neem, and green tea mouthwashes in patients with mild to moderate gingivitis. Methods: A randomized control trial was conducted on 123 patients, attending dental OPD, after taking a detailed history, and an initial baseline clinical examination was done, then subjects were randomly divided into three treatment groups. Group A- 0.2% Chlorhexidine, Group B- 2% Neem, Group C- 0.5% Green tea. Study participants were trained to use the provided mouthwash for 15 seconds after brushing, twice daily. Baseline data was further followed by the 4th week, 8th week, and 12th week. Any side effects and complaints were recorded using a questionnaire at every follow-up. Results were considered significant when p-value (p <0.05). Results: Study participants range from 18 to 29 years, results show an overall reduction from the baseline scores and also marked clinical improvement was seen in the overall oral health status in all three management groups, Inter-comparison was done by using repeated ANOVA test, and the post hoc test showed that within management groups was found to be statistically significant (p = .000) that when Group A compared with both Group B (Neem) and Group C (Green tea) at the 12thweek showed significant results. All of the study participants were asked about their overall remarks for using particular mouthwashes, their accessibility, and taste alterations, and their experience of using their particular mouthwashes, which showed positive outcomes. Conclusion: All the mouthwashes were equally effective in reducing plaque-induced gingivitis. The advantage of using natural products with no side effects and being inexpensive is that they are also non-toxic.